The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41419-018-0768-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of tumor suppressor gene CDKN1A by oncogenic long non-coding RNA SNHG1 in cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is the as the most frequently observed biliary tract malignancy, which has low survival rate in addition to constrained treatment options; nevertheless, the fundamental molecular phenomenon underlying malignant progression of CCA is quite ambiguous. Recently long non-coding RNAs (lncRNAs) have been found to have significant regulatory functions in several human cancers. Herein, we have figured out that lncRNA SNHG1, with substantially enhanced expression in CCA, is capable of acting as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…After that, we assessed the binding motifs of several recently discovered CCA-related lncRNAs' promoters by JASPAR and found USF1 might bind some lncRNAs' promoters with relative high scores (Table 3) as well as proliferation in vitro and in vivo, AFAP1-AS1 promotes the CCA proliferation and metastasis while providing potential therapeutic target for CCA. [29][30][31][32] LncRNA ZFAS1, antisense to the 5' end of ZNFX1 promoter, has been demonstrated aberrantly expressed in many cancers and equipped with different functional mechanisms, which we have previously described. As one of our previous works shows that a larger number of studies have indicated that the ZFAS1 is F I G U R E 4 ZFAS1 regulated USF1 expression by directly binding miR-296-5p as a ceRNA manner and affected tumour growth in vivo.…”
Section: Usf1 Induces Cca-related Transcription By the Prediction Omentioning
confidence: 78%
See 1 more Smart Citation
“…After that, we assessed the binding motifs of several recently discovered CCA-related lncRNAs' promoters by JASPAR and found USF1 might bind some lncRNAs' promoters with relative high scores (Table 3) as well as proliferation in vitro and in vivo, AFAP1-AS1 promotes the CCA proliferation and metastasis while providing potential therapeutic target for CCA. [29][30][31][32] LncRNA ZFAS1, antisense to the 5' end of ZNFX1 promoter, has been demonstrated aberrantly expressed in many cancers and equipped with different functional mechanisms, which we have previously described. As one of our previous works shows that a larger number of studies have indicated that the ZFAS1 is F I G U R E 4 ZFAS1 regulated USF1 expression by directly binding miR-296-5p as a ceRNA manner and affected tumour growth in vivo.…”
Section: Usf1 Induces Cca-related Transcription By the Prediction Omentioning
confidence: 78%
“…LncRNAs are one huge class of those newly focused specific molecules to have crucial impact on CCA, and their functional modes were relatively unique to the classic protein‐coding factors, which could regulate gene transcription and post‐transcription without coding proteins. Some of the CCA‐related lncRNAs were excavated to play vital roles during the genesis and development of CCA recent years, for instance lncRNA TUG1 suppression inhibits CCA metastasis potential by reversing EMT, SNHG1 binds to the histone methyltransferase enhancer of EZH2 and PRC2 to alter the CCA migration as well as proliferation in vitro and in vivo, AFAP1‐AS1 promotes the CCA proliferation and metastasis while providing potential therapeutic target for CCA …”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that SPRY4-IT1 exhibits tremendous potentiality for the diagnosis and treatment of CCA and likely functions as a novel diagnostic biomarker and intervention target. experiment was also conducted to prove its carcinogenic function (Han et al, 2018;Yu, W. D. et al, 2018;Yu, Y. et al, 2018aYu, Y. et al, , 2018b. Similar to the above, small nucleolar RNA host gene 1 (SNHG1), which is situated at 11q12.3 region of the human chromosome Zhang, D. et al, 2018;Zhang, R. et al, 2018;, was also verified highly expressed in both CCA tissues and cells.…”
mentioning
confidence: 72%
“…Similar to the above, small nucleolar RNA host gene 1 ( SNHG1 ), which is situated at 11q12.3 region of the human chromosome (Zhang, C. et al, ; Zhang, D. et al, ; Zhang, F. et al, ; Zhang, N. et al, ; Zhang, R. et al, ; Zhang, X. N. et al, ), was also verified highly expressed in both CCA tissues and cells. Moreover, SNHG1 knockdown inhibited proliferation and migration, delayed cell‐cycle, and attenuated apoptosis as well (Yu, W. D. et al, ; Yu, Y. et al, , ). According to these results, both PVT1 and SNHG1 exert significant functions in CCA oncogenesis and probably represent outstanding targets for CCA intervention.…”
Section: Roles and Clinical Values Of Lncrnas In Cholangiocarcinomamentioning
confidence: 99%
“…Epigenetic regulation of disease has seen an increase of focus since the discovery of non-coding RNAs. It has been found that epigenetic silencing of tumor suppressor genes results in CCA oncogenesis (7). CCA is regulated by multiple biological factors, including various miRNAs, so identifying post-transcriptional targets for reduction of CCA progression is of high importance.…”
Section: Epigenetics and Post-transcriptional Modificationmentioning
confidence: 99%